Spatial mapping of protein composition and tissue organization: a primer for multiplexed antibody-based imaging - Hickey, John W.; Neumann, Elizabeth K.; Radtke, Andrea J.; Camarillo, Jeannie M.; Beuschel, Rebecca T.; Albanese, Alexandre; McDonough, Elizabeth; Hatler, Julia; Wiblin, Anne E.; Fisher, Jeremy; Croteau, Josh; Small, Eliza C.; et al. (Nature methods, 2022)
Tissues and organs are composed of distinct cell types that must operate in concert to perform physiological functions. Efforts to create high-dimensional biomarker catalogs of these cells have been largely based on single-cell sequencing approaches, which lack the spatial context required to understand critical cellular communication and correlated structural organization. To probe in situ biology with sufficient depth, several multiplexed protein imaging methods have been recently developed. Though these technologies differ in strategy and mode of immunolabeling and detection tags, they commonly utilize antibodies directed against protein biomarkers to provide detailed spatial and functional maps of complex tissues. As these promising antibody-based multiplexing approaches become more widely adopted, new frameworks and considerations are critical for training future users, generating molecular tools, validating antibody panels, and harmonizing datasets. In this Perspective, we provide essential resources, key considerations for obtaining robust and reproducible imaging data, and specialized knowledge from domain experts and technology developers. This Perspective offers guidance for robust and reproducible antibody-based highly multiplexed tissue imaging.